The Knowable and the Unknowable: Modern Science, Nonclassical Thought, and the "Two Cultures" - Plotnitsky, Arkady (Ann Arbor, MI University of Michigan Press, 2002)
This book investigates the relationships between modern mathematics and science (in particular, quantum mechanics) and the mode of theorizing that Arkady Plotnitsky defines as "nonclassical" and identifies in the work of Bohr, Heisenberg, Lacan, and Derrida. Plotinsky argues that their scientific and philosophical works radically redefined the nature and scope of our knowledge. Building upon their ideas, the book finds a new, nonclassical character in the "dream of great interconnections" Bohr described, thereby engaging with recent debates about the "two cultures" (the humanities and the sciences).Plotnitsky highlights those points at which the known gives way to the unknown (and unknowable). These points are significant, he argues, because they push the boundaries of thought and challenge the boundaries of disciplinarity. One of the book's most interesting observations is that key figures in science, in order to push toward a framing of the unknown, actually retreated into a conservative disciplinarity. Plotnitsky's informed, interdisciplinary approach is more productive than the disparaging attacks on postmodernism or scientism that have hitherto characterized this discourse.Arkady Plotnitsky is Professor of English and Director, Theory and Cultural Studies Program, Purdue University. Trained in both mathematics and literary theory, he is author of several books, including In the Shadow of Hegel: Complementarity, History and the Unconscious and Reconfigurations: Critical Theory and General Economy.
Keywords: Philosophy